2014
DOI: 10.1167/iovs.13-12261
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Prognostic Factors Predict Rapid Visual Field Deterioration in Glaucoma

Abstract: Patients with more severe glaucomatous damage, as measured by both visual field or optic disc cupping and older age, are at highest risk for rapid worsening of the disease, as are African Americans compared to Caucasians. More aggressive treatment of such patients should be considered to prevent visual disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 21 publications
3
33
1
Order By: Relevance
“…Recent studies have reported that CH is a stronger risk factor for the progression of glaucoma than CCT26, and indeed, in the current study, CH was included in both model ORA and model ORA_CST . Baseline VF damage may43949 or may not405051 be related to faster VF progression; however, in the current study, mTD in the initial VF was not included in any of the optimal models.…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies have reported that CH is a stronger risk factor for the progression of glaucoma than CCT26, and indeed, in the current study, CH was included in both model ORA and model ORA_CST . Baseline VF damage may43949 or may not405051 be related to faster VF progression; however, in the current study, mTD in the initial VF was not included in any of the optimal models.…”
Section: Discussionmentioning
confidence: 90%
“…[7, 13] Similarly, in another study, self-described race was no longer a significant predictor of “fast VF progression,” defined as a component decay rate of ≥36%/y, when baseline cup disc ratio and VF parameters were included in the multivariable model. [23, 24] These studies did not specifically examine the interaction between race and IOP in predicting the development of VF damage.…”
Section: Discussionmentioning
confidence: 99%
“…[27,28] Explanations for this relationship require further investigation but may have to do with ethnic differences in central corneal thickness, [29] IOP, stage at diagnosis, or medication adherence, [30,31] which themselves are risk factors for glaucoma or glaucoma progression. [5,6,32] Haitian participants did have a somewhat higher treated maximum IOP (mean = 19.5) than white participants (mean = 18.7) but not statistically significantly so.…”
Section: Discussionmentioning
confidence: 99%